SYNCHRONOUS PWM CONTROL OF SYMMETRICAL DUAL THREE-PHASE DRIVE IN THE OVERMODULATION ZONE - Oleschuk V.I.; Sizov A. (Problems of the Regional Energetics)
The analysis of operation of symmetrical six-phase (dual three-phase) ac drive system (which is a promising solution for the medium-power and high-power applications) with synchronized pulse-width modulation (PWM) during overmodulation has been performed. The induction machine of this system topology has two sets of windings spatially shifted by 60 electrical degrees with isolated neutral points, which are connected with two standard three-phase inverters. Algorithms of synchronized PWM provide continuous synchronization of the phase voltage of the system in the zone of overmodulation. Simulation results are given for dual three-phase systems with two discontinuous versions of synchronized PWM, and with combined synchronized scheme of pulsewidth modulation.